2021
DOI: 10.3390/nu13103607
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Individual and Combined Low Dose Beta-Carotene and Metformin Treatments against High-Fat Diet-Induced Responses in Mice

Abstract: Anti-obesity activity has been reported for beta-carotene (BC) supplementation at high doses and metformin (MET). We studied whether BC treatment at a closer to dietary dose and MET treatment at a lower than therapeutic dose are effective in ameliorating unwanted effects of an obesogenic diet and whether their combination is advantageous. Obesity-prone mice were challenged with a high-fat diet (HFD, 45% energy as fat) for 4 weeks while receiving a placebo or being treated orally with BC (3 mg/kg/day), MET (100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 60 publications
3
5
0
Order By: Relevance
“…Some studies have reported that both Met and Mir can individually activate BAT thermogenesis, 27–29,39,40 while others have shown that only Mir but not Met promotes BAT thermogenesis 39,41,42 . Our study was consistent with the latter, finding that Mir but not Met enhanced BAT thermogenesis in both mouse models.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Some studies have reported that both Met and Mir can individually activate BAT thermogenesis, 27–29,39,40 while others have shown that only Mir but not Met promotes BAT thermogenesis 39,41,42 . Our study was consistent with the latter, finding that Mir but not Met enhanced BAT thermogenesis in both mouse models.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, an increase in browning of WATs by Met/Mir treatment also contributed to this greater EE, leading to lower body adiposity in the treatment model. This was an intriguing finding given that Met alone did not significantly promote browning of scWAT in HFD‐fed mice in either treatment or prevention models, consistent with the literature 41 . In addition, Mir has been found to augment scWAT browning in chow‐fed 40 and DIO 31 mice, and it was also observed to increase WAT browning in humans with obesity 43,44 but interestingly, not in healthy individuals 28 .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…A previous study reported that lutein supplementation up to 1,000 mg/kg/day is non‐toxic in mice models (Nidhi & Baskaran, 2013). The concentrations of lutein and orlistat were selected based on the reports of previous studies (Choi et al, 2016; Liu et al, 2017; Stojnić et al, 2021). The lutein concentration of 300 μM is equivalent to 1.5 mg/kg body weight and 500 μM is equivalent to 2.8 mg/kg body weight.…”
Section: Methodsmentioning
confidence: 99%
“…Since the dietinduced obesity model closely mimics the development of obesity in humans and is considered an essential tool for understanding the molecular mechanism (Collins, Martin, Surwit, & Robidoux, 2004;van der Klaauw & Sadaf Farooqi, 2015), we employed high-fat-fed (Nidhi & Baskaran, 2013). The concentrations of lutein and orlistat were selected based on the reports of previous studies (Choi et al, 2016;Liu et al, 2017;Stojni c et al, 2021). The lutein concentration of 300 μM is equivalent to 1.5 mg/kg body weight and 500 μM is equivalent to 2.8 mg/kg body weight.…”
Section: Introductionmentioning
confidence: 99%